Experimental Investigation for Cutting Force by Optimizing Machining Parameters with Taguchi Method in Turning of AISI 4340 Steel - Jain, Pankaj; Kuldeep,; Kumar, Suryabhan (International Journal of Computer Sciences and Engineering, 2025)
To increase the productivity in machining industries demand for minimum cutting force, better surface finish and accuracy has been increasing rapidly in recent years. Therefore, this paper focuses on an effective approach for the optimization of process parameters. This paper investigate the effect of cutting parameters such as cutting speed, feed and depth of cut on the performance characteristics cutting force in turning of AISI 4340 steel with brazed tungsten carbide turning tools. The effects of the process parameters on performance characteristics cutting force are investigated by using Taguchi’s L9 orthogonal array and analysis of variance (ANOVA). The results show that the depth of cut is majorly affecting the cutting force, followed by feed rate. The experimental data were further analyzed and to correlate with cutting parameters using linear regression analysis. Finally machined surface of the workpiece were examined under optimal cutting conditions such as CV = 75 m/min, FR = 0.4 mm/rev and DOC = 0.5 mm) and found the minimum force is equal to 5.09kg.